Multi-parameter analysis of curing cycle for GNPs/glass fabric/ epoxy laminated nanocomposites (Fracture and Structural Integrity, 2019)
In this study, a multi-parameter analysis, using Taguchi method for design of experiments, has been conducted to investigate the optimum curing conditions for GNPs/E-glass fabric/epoxy laminated nanocomposites. The independent variables in the L25 Taguchi orthogonal array were heating rate, curing temperature and curing time, addressing five levels each. Tensile and 3-point bending tests were performed for each experiment number (run number) of the Taguchi L25. The analysis shown that the most significant parameter for tensile strength is the time and for flexural strength is the temperature. Also, it shown that the optimum performance was obtained for temperature values greater than the glass transition temperature Tg.
Keywords: Polymer-matrix composites; Nanocomposites; Graphene nanoplatelets; Curing; Mechanical testing; Multi-parameter analysis